2018
DOI: 10.1111/dom.13267
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of canagliflozin as add‐on therapy to a glucagon‐like peptide‐1 receptor agonist in Japanese patients with type 2 diabetes mellitus: A 52‐week, open‐label, phase IV study

Abstract: Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors and glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are antihyperglycaemic agents with weight‐lowering effects. The efficacy and safety of the SGLT2 inhibitor canagliflozin as add‐on therapy in Japanese patients with type 2 diabetes mellitus (T2DM) and inadequate glycaemic control with a GLP‐1RA (≥12 weeks) were evaluated in this phase IV study. Patients received canagliflozin 100 mg once daily for 52 weeks. Efficacy endpoints included change in glycated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…In the AWARD-10 study, addition of dulaglutide 1.5 mg to SGLT-2i therapy was associated with significant reductions compared with placebo in body weight (-3.1 vs -2.1 kg; p = 0.028) and systolic BP (-4.5 vs -1.4 mm Hg; p = 0.021) [64]. Other studies in which SGLT-2i therapy was added to GLP-1RA treatment showed similar results, with significant improvements in BP and body weight (Table 1) [62,63,67].…”
Section: Non-glycemic Effectsmentioning
confidence: 84%
See 2 more Smart Citations
“…In the AWARD-10 study, addition of dulaglutide 1.5 mg to SGLT-2i therapy was associated with significant reductions compared with placebo in body weight (-3.1 vs -2.1 kg; p = 0.028) and systolic BP (-4.5 vs -1.4 mm Hg; p = 0.021) [64]. Other studies in which SGLT-2i therapy was added to GLP-1RA treatment showed similar results, with significant improvements in BP and body weight (Table 1) [62,63,67].…”
Section: Non-glycemic Effectsmentioning
confidence: 84%
“…In the Assessment of Weekly Administration of LY2189265 (dulaglutide) in Diabetes-10 (AWARD-10) study, addition of the GLP-1RA dulaglutide to stable SGLT-2i therapy was associated with significantly greater reductions in A1c from baseline to 24 weeks (-1.21% and -1.34% for the 0.75-mg and 1.5-mg doses, respectively) compared with placebo (-0.54%; p < 0.0001 for both doses) [64]. In real-world observational studies, in which an SGLT-2i was added to GLP-1RA background therapy (with or without other glucose-lowering therapies), the mean incremental change in A1c with the combination ranged from -0.39% to −1.5% [62,63,[65][66][67].…”
Section: Glycemic Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Os desfechos mostraram reduções significativas na HbA1c em todos os momentos, incluindo redução de peso e de pressão arterial. Contudo, foram identificados eventos adversos como candidíase vulvovaginal e hipoglicemia em 10% dos pacientes (HARASHIMA et al, 2018).…”
Section: Complementaresunclassified
“…8 Several national and international studies have demonstrated the long-term effectiveness of canagliflozin as an add-on to dipeptidyl peptidase-4 inhibitors and glucagonlike peptide-1 receptor agonists. 10,11 Canagliflozin is commonly used at daily doses of 100 and 300 mg. 12 The drug has demonstrated remarkable reduction in blood pressure, body weight and has lower risk of hypoglycaemia. 13 Kadowaki et al (2018) have reported the long-term safety and efficacy of canagliflozin, as an add-on to teneligliptin, in Japanese T2DM patients with inadequate glycemic control.…”
mentioning
confidence: 99%